Jathilan Horse Dance: Spirit Possesion Beliefs and Practices in The Present-day Java - Rapoport, Eva (Center for Southeast Asian Social Studies (CESASS), 2018)
Jathilan is one of the names for traditional Javanese trance dance which takes its roots in the most archaic levels of local culture but remains very popular nowadays. It is also described as a horse dance for the horse effigies made of woven bamboo are the hallmark props used by the performers. Horse dance is a part of the folk culture, still untouched by institutionalization or commodification; it can be performed for both ritual and entertainment purposes. Trance is its main attraction, though through the lens of local beliefs it is interpreted in terms of spirit possession thus it is understood that spirits can enter performers? bodies and fulfill their needs while being manifest in material world, but also allow the dancers to perform various feats demonstrating invulnerability to physical harm (like eating glass, walking over hot coals, being whipped or even ran over by a motorcycle).The purpose of this paper is to provide a thorough description of how trance in jathilan is performed and understood, based on existing literature, practitioners? first-hand accounts and numerous performances observed and documented; but also to consider it in the wider context of Javanese beliefs and practices involving spirits, possession, and exorcism, which persist alongside with Islam.